The Cham Minority Group Cambodia Division Within Introduction to Comtemporary Changes in Cham Communiries Cham Jahed in Mosque for Friday Prayer - Seise, Claudia (UIN Sunan Kalijaga Yogyakarta, 2007)
The Cham forms an ethnic minority group, both in Vietnam and Cambodia. In my research paper I will focus on the Cham in Cambodia, who emigrated from their lost homeland -the Champa Kingdom in present day Vietnam. The Cham in Cambodia number around 200,000 people and make up two percent of the country's population.